Implementasi Aplikasi Penjualan dan Persediaan Obat Berbasis Desktop (Studi Kasus : Apotek Wisa Farma) - Aas Sriyani (Institut Shanti Bhuana, 2024)
This research aims to refine and implement a desktop- based sales and inventory application at Wisa Farma Pharmacy to enhance operational efficiency and data accuracy. The application was developed using Visual Basic .NET and MySQL to replace the error-prone manual recording system. The methodology involved analyzing the pharmacy's needs, designing an intuitive interface, and integrating a database . As a result, the application improves workflow efficiency and service quality at the pharmacy by reducing waiting times and recording errors. The solutions offered include minimizing human errors, improving operational efficiency, and enhancing decision-making. It is recommended that the pharmacy use licensed software, train employees, perform regular maintenance, and develop additional features such as electronic prescription management and digital payment integration to further improve efficiency and service quality.